2013
DOI: 10.1177/0739456x13482978
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Transportation Outcomes for LEED Projects

Abstract: The article first estimates models of mode choice and average trip length for 239 diverse mixed-use developments in six diverse regions. It then applies these models to twelve Leadership in Energy and Environmental Design for Neighborhood Development (LEED-ND) pilot projects to predict approximate vehicle miles of travel (VMT) per person trip. Finally, it compares LEED-ND values to regional average values from the National Household Travel Survey. The VMT per person trip, for LEED-ND projects, ranges from 24 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Such interactive relationships generated between data will violate the assumption that all variables in the traditional regression model are independent of each other, so that the standardized error obtained by the traditional regression model will deviate from the actual value, and the wrong standardized coefficient will be obtained [35] The MLM model can solve this problem, and is widely used in education, public health, and other research fields to process data groups with correlation between variables. In recent years, MLM has been used increasingly in urban studies [36][37][38]. The hierarchical structure diagram of MLM used in this study is provided in Fig.…”
Section: Fig 2 Patronage Distribution Of Rail Stations In Shanghaimentioning
confidence: 99%
“…Such interactive relationships generated between data will violate the assumption that all variables in the traditional regression model are independent of each other, so that the standardized error obtained by the traditional regression model will deviate from the actual value, and the wrong standardized coefficient will be obtained [35] The MLM model can solve this problem, and is widely used in education, public health, and other research fields to process data groups with correlation between variables. In recent years, MLM has been used increasingly in urban studies [36][37][38]. The hierarchical structure diagram of MLM used in this study is provided in Fig.…”
Section: Fig 2 Patronage Distribution Of Rail Stations In Shanghaimentioning
confidence: 99%
“…A major obstacle to achieve sustainable mobility in Sweden is the urban form. Many neighbourhoods, towns and cities, as elsewhere in the developed countries Inversely, transportation professionals use land uses or density of development (usually as number of jobs and residents) to predict trip generation [55][56][57]. The trip generation models are based on empirical research on travel patterns from specific land uses.…”
Section: Introductionmentioning
confidence: 99%
“…The trip generation models are based on empirical research on travel patterns from specific land uses. The "Trip Generation Manual" [56] compiles and continuously updates the empirical knowledge on the effect of hundreds of land uses. The D-variables are also used to estimate trip generation rates [55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, current notions of how to reduce energy demand and mitigate greenhouse gas (GHG) emissions also align with Jacobs' ideas of a diverse and economically successful urban area (Seto et al 2014;Otkay, 2012;Kennedy, 2011;Talen, 2011;Jabareen, 2006). Indeed some quantitative analysis has been conducted in this regard; for example, Ewing et al (2013) found that mixed-use developments built to LEED-ND (Leadership in Energy and Environmental Design -New Development) standards have been estimated to reduce per capita vehiclekilometers traveled (VKT) by 24-60%. Porter (2009) suggests that a 12% reduction in national transportation-related GHGs through aggressive implementation of compact land use approaches (i.e., transit-oriented development).…”
Section: Introductionmentioning
confidence: 99%